An Analysis of Decentralization, Regional Dependence, Regional Independence, Effectiveness and Efficiency of Pad, Expenditure Efficiency, and Shopping Harmony in Assessing Regional Financial Performance (Case Study in Government Pekanbaru City) - Mustafa Ahmad Zuhri; Anggi Pratama; Rahima Br. Purba (Rowter Journal, 2022)
This research was conducted by Pekanbaru City Government. This study aims to determine the financial performance of the Pekanbaru City Government for the Fiscal Year 2016 to 2020. This research uses a descriptive method. Data analysis uses local government financial ratios with an income and expenditure approach consisting of the degree of decentralization, the ratio of regional financial dependence, the ratio of regional financial independence, and the effectiveness and efficiency ratio of Regional Original Income (PAD), efficiency ratios and spending compatibility. The results show that the degree of decentralization is in the medium category, the level of regional financial dependence is in the very high category, the level of regional financial independence is in the low category with a consultative relationship pattern, and the effectiveness level of Regional Original Revenue is in the ineffective category, the efficiency level of Regional Original Revenue is in the inefficient category, the level of spending efficiency is in the efficient category